Private Debt and the Role of Venture Capital and Private Equity Sponsors - Buchner, Axel; Espenlaub, Susanne; Khurshed, Arif; Mohamed, Abdulkadir (Management Science, 2024)
This is the first study examining the key role played by venture capital and private equity (VCPE) firms in the private debt market. Private debt funds invest in companies owned (sponsored) by VCPEs and in other companies without VCPE sponsors. Using novel data, we find that private debt without VCPE sponsors generates a premium. Further analysis shows that this sponsorless premium compensates for higher risk and costs of risk mitigation as sponsorless lenders adopt a more hands-on approach emulating VCPE sponsors’ roles. Our results are robust and provide important lessons for investors and investee firms in private debt, venture lending, and VCPE. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4664 .